2018
DOI: 10.1111/nph.15427
|View full text |Cite
|
Sign up to set email alerts
|

The essential chloroplast ribosomal protein uL15c interacts with the chloroplast RNA helicase ISE2 and affects intercellular trafficking through plasmodesmata

Abstract: Chloroplasts retain part of their ancestral genomes and the machinery for expression of those genomes. The nucleus-encoded chloroplast RNA helicase INCREASED SIZE EXCLUSION LIMIT2 (ISE2) is required for chloroplast ribosomal RNA processing and chloro-ribosome assembly. To further elucidate ISE2's role in chloroplast translation, two independent approaches were used to identify its potential protein partners. Both a yeast two-hybrid screen and a pull-down assay identified plastid ribosomal protein L15, uL15c (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…To identify molecular pathways that regulate PD transport, we and others have conducted forward genetic screens. These screens to identify factors controlling transport through PD have repeatedly revealed that chloroplasts influence PD transport (Provencher et al, 2001;Benitez-Alfonso et al, 2009;Zambryski, 2010, 2012;Burch-Smith et al, 2011;Stonebloom et al, 2012;Brunkard et al, 2013;Carlotto et al, 2016;Bobik et al, 2019). This has led to a paradigm shift, focusing less on the role of structural changes directly at PD and more on how cellular physiology influences the function of PD.…”
mentioning
confidence: 99%
“…To identify molecular pathways that regulate PD transport, we and others have conducted forward genetic screens. These screens to identify factors controlling transport through PD have repeatedly revealed that chloroplasts influence PD transport (Provencher et al, 2001;Benitez-Alfonso et al, 2009;Zambryski, 2010, 2012;Burch-Smith et al, 2011;Stonebloom et al, 2012;Brunkard et al, 2013;Carlotto et al, 2016;Bobik et al, 2019). This has led to a paradigm shift, focusing less on the role of structural changes directly at PD and more on how cellular physiology influences the function of PD.…”
mentioning
confidence: 99%
“…In order to reveal whether the high transformation rates were a result of a specific susceptibility of C. reflexa to A. rhizogenes we exposed far-red light induced stems to Agrobacterium tumefaciens carrying a GFP gene in the T-DNA of a binary plasmid (Bobik et al, 2019) using the same setup. Only very weak background fluorescence was seen in this case in the orange channel and in the blue channel, while the high intensity of green fluorescence in a ring corresponding to the adhesive disk indicated that the GFP was expressed in this tissue as a result of the transformation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As our experiments show, the protocol works with both, A. rhizogenes and A. tumefaciens and allows the expression of reporter proteins from different binary vectors and under the control of different promoters. The T-DNA of pRedRoot, a binary vector developed for A. rhizogenes , contains the dsRed protein under control of the Ubi10 promoter (Libiakova et al, 2018), while the A. tumefaciens line used by Bobik et al (2019) contains a GFP gene controlled by the 35S promoter. Both promoters allow strong constitutive expression of transgenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…prps21 is a viable mutant with a relatively strong defect in shoot growth and has reduced levels of 16S and 23S rRNAs [56]. Similarly, co-suppression lines of PRPL15 in Arabidopsis and a knockout line of prps15 in tobacco have shown reductions in 16S and 23S rRNA levels [57,58]. PALE CRESS (PAC) binds to 23S rRNA and promotes 50S subunit biogenesis, while the pac mutants dramatically reduce levels of both 16S and 23S rRNAs [59].…”
Section: Discussionmentioning
confidence: 99%